Absence of IgG antibodies among high-risk contacts of two confirmed cases of Crimean-Congo haemorrhagic fever in the autonomous region of Madrid (Spain). Issue 10 (October 2020) - Latasa, Pello; de Ory, Fernando; Arribas, José Ramón; Sánchez-Uriz, Maria Ángeles; Sanchez-Arcilla, Ignacio; Ordobás, María; Negredo, Anabel; Trigo, Elena; Delgado, Pilar; Marzola, Marco; Lopaz, Maria Ángeles; Sánchez-Seco, María Paz; et al.
Abstract: Crimean-Congo haemorrhagic fever (CCHF) is a widely distributed tick-borne disease. In Spain, the disease has emerged as outbreak associated with high-risk exposures. Our goal was to evaluate the prevalence of antibodies against the CCHF virus (CCHFV) in high-risk contacts. A cross-sectional study was conducted. Three hundred eighty-six high-risk contacts were identified comprising family contacts and hospital workers who had attended the cases. Fifty-seven cases with closer exposure were selected. However, forty-nine cases participated in the study. IgG antibodies were detected by immunoenzymatic techniques. All determinations tested negative for anti-CCHFV IgG antibodies. Most of the responders were women (73.5%), and belong to the intensive care department (53.1%). In relation to other possible sources of exposures, 18.4% travelled to countries with CCHF transmission risk. No CCHF positivity was recorded among selected high-risk contacts. This highlights the importance of standard precautions which might have protected healthcare workers and care providers from CCHF infection.